2019
DOI: 10.3168/jds.2019-16451
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association for milk production traits and somatic cell score in different lactation stages of Ayrshire, Holstein, and Jersey dairy cattle

Abstract: We performed genome-wide association analyses for milk, fat, and protein yields and somatic cell score based on lactation stages in the first 3 parities of Canadian Ayrshire, Holstein, and Jersey cattle. The genome-wide association analyses were performed considering 3 different lactation stages for each trait and parity: from 5 to 95, from 96 to 215, and from 216 to 305 d in milk. Effects of single nucleotide polymorphisms (SNP) for each lactation stage, trait, parity, and breed were estimated by back-solving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 73 publications
8
44
0
Order By: Relevance
“…A GWAS was done for GWRR in each breed/sex population, where the primary focus was identifying significant genomic regions by estimating variance explained by overlapping 10 SNP windows. A Manhattan plot of variance explained by window can be found in Figure 4, with significance considered at “low” (0.3%) and “high” (0.5%) variance explained thresholds, which have been previously used to establish significance (Medeiros de Oliveira Silva et al., 2017; Oliveira et al., 2019). Variance explained by the top five windows in each population can be found in Table 4, alongside genes mapped inside each window.…”
Section: Resultsmentioning
confidence: 99%
“…A GWAS was done for GWRR in each breed/sex population, where the primary focus was identifying significant genomic regions by estimating variance explained by overlapping 10 SNP windows. A Manhattan plot of variance explained by window can be found in Figure 4, with significance considered at “low” (0.3%) and “high” (0.5%) variance explained thresholds, which have been previously used to establish significance (Medeiros de Oliveira Silva et al., 2017; Oliveira et al., 2019). Variance explained by the top five windows in each population can be found in Table 4, alongside genes mapped inside each window.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the significant genomic regions found in this study are located on BTA14 within or harboring the DGAT1 , FOXH1, and CYHR1 genes. The DGAT1 gene is well known due to its strong association with milk production traits, especially milk fat [27,28,29]. The CYP11B1 gene, which is a CYHR1 paralogous [30], has been reported to be associated with milk fat in buffalo [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RR models based on LP are sensitive to few records per cow, mainly for estimations at the extremes of the lactation curve (Meyer, 2005;Misztal, 2006). This problem may be reduced using AR processes (Oliveira, Cant, et al, 2019). Another alternative to LP is the splines functions (Meyer, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The genetic correlation between TD may differ from unit, meaning that the expression at each DIM may have different additive genetic variance. Recently Oliveira, Cant, et al () reported that there are different genomic regions affecting milk‐related traits along and across lactations. In this context, RR model enables the variance modelling over a continuous scale, assuming that genetic correlations may change over time.…”
Section: Discussionmentioning
confidence: 99%